Comparison of the Effectiveness of Teaching Strategies Based on Emotion-Oriented Couple on Communication Patterns of Couples - S Ghorbanshirroudi; A Amini; J Khalatbari (Armaghane Danesh Bimonthly Journal, 2023)
Background & aim: The family is the place to satisfy various physical, intellectual and emotional needs, and having awareness of biological and psychological needs and knowing how to satisfy them and being equipped with techniques and recognizing biological and psychological tendencies is an undeniable necessity. The present study was conducted with the aim of comparing the effectiveness of teaching emotion management strategies based on emotionally focused couple therapy (EFT) and schema-based couple therapy on couples' communication patterns.